PbS/IGZO hybrid structure photo‐field‐effect transistor with high performance. (1st November 2018) - Meng, Ying; Wang, Jiawei; Ming, Anjie; Wang, Yinghui; Shi, Xuewen; Li, Molin; Wang, Weibing; Li, Ling
Abstract : To optimise the performance of photo‐field‐effect transistor, a back‐gate hybrid structure was developed. In this hybrid phototransistor, lead sulphide (PbS) thin film was prepared using physical vapour deposition as a photosensitive layer. Discontinuous and uniform PbS film was obtained by controlling the deposition rate and time of PbS powders. Amorphous indium gallium zinc oxide (IGZO) with high mobility was used as an active layer. In this work, The hybrid structure phototransistor shows an excellent performance: device mobility ( μ ) reach 8.7 cm 2 V −1 s −1, and responsivity achieve 2.7 × 10 4 A/W in visible spectrum and 5.7 A/W in near‐infrared spectrum, respectively. Furthermore, the transistor exhibits detectivity up to 2.79 × 10 13 cmHz 1/2 W −1 . The device also exhibits characteristics of the ideal diode: the saturation current of the diode is as small as 0.422 nA, and the responsivity of diode is ∼0.74 A/W. Simplified manufacturing processes effectively reduce the cost of fabricated device and provide better device stability.